2010
DOI: 10.1063/1.3447874
|View full text |Cite
|
Sign up to set email alerts
|

Relative phase interactions of two copropagating laser beams in underdense plasmas at different intensities and spot sizes

Abstract: The mutual interactions of two copropagating laser beams at a relative phase are studied using a two-dimensional fluid code. The interactions are investigated in underdense plasma at selected beam configurations and beam parameters for two separate nonlinearities, i.e., the ponderomotive and the relativistic nonlinearity. The selected beam configurations are introduced by different initial transverse spot size perturbations ͑finite and infinite͒ and different initial transversal intensity distributions ͑nonuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…However, although our results are unlikely to have any experimental implications for photon-photon scattering in vacuum in the near future, their implications in photon-photon scattering in non-linear optical media [27], cavities [28], gases [29], plasmas [30][31][32][33] and with Rydberg atoms [34,35] could be observable.…”
Section: Discussionmentioning
confidence: 79%
“…However, although our results are unlikely to have any experimental implications for photon-photon scattering in vacuum in the near future, their implications in photon-photon scattering in non-linear optical media [27], cavities [28], gases [29], plasmas [30][31][32][33] and with Rydberg atoms [34,35] could be observable.…”
Section: Discussionmentioning
confidence: 79%
“…In the relativistic regime, similar interaction properties * Electronic address: zcangtao@iapcm.ac.cn † Electronic address: taiwu.huang@szu.edu.cn have also been found in plasmas [26][27][28][29][30][31][32]. Plasma can be regarded as a kind of nonlinear medium that is already breakdown and in principle can tolerate ultra-strong laser fields.…”
Section: Introductionmentioning
confidence: 88%
“…Ren et al observed the spiraling interaction of two laser beams with crossed polarization directions [27,28]. Mahdy studied the interaction process of two laser beams that are out of phase at different intensities and spot sizes [29]. However, so far, the effects of the relative phase difference (φ) between the two coherent laser beams are not explored yet.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, we simulated the propagation of a fs beam with an initial input energy E 01 = 2.4µJ in air plasma (n e = 10 15 cm −3 ). We conducted this simulation by numerically solving [16] a 2D envelope equation [17] in the Quasi Statics Approximation (QSA) coordinate [18], the result of this simulation is shown in figure 1. As displayed in this figure, a structure of a periodically self-focused and de-focused beam is clearly demonstrated at propagation time t = 120ps, the demonstrated structure is the ultrashort filament formation in underdesnse plasma.…”
Section: The Formation Of Ultrashort Filament In Underdesnse Plasmamentioning
confidence: 99%